EFEKTIVITAS PENGGUNAAN SEMPOA DALAM KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR - Sindi Meli Nur Afni; Avrilia Vega Ray; Ayu Melia Febianti; Aurellisa Maira Sari; Ivanna Priscilla Avrinata; Ahmad Fu'adin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
Mathematics is a science that improves the human mindset to think more systematically. Therefore, Mathematics has been studied from an early age so that children are more accustomed to thinking systematically and critically. The material taught for early childhood is about addition, subtraction, multiplication and division. To simplify the calculation of addition, subtraction, multiplication and division, Abacus can help children complete these calculations quickly and accurately. However, unfortunately there are still many children who do not even understand how to use the Abacus because learning to use the Abacus to facilitate calculations in elementary school is no longer preserved. Based on the data we took from ISOLA elementary school students, the average student answering math problems is quite longer than students who can use Sempoa. The average difference is large enough that it can be concluded that students who can use the Abacus are faster at calculating correctly than ordinary students who cannot use the Abacus. Therefore, it is necessary to increase the use of Sempoa among elementary school children to improve children's mindset. It would be better if Abacus can be taught directly by teachers or teachers at the elementary school level so that all children are accustomed to counting quickly and precisely.